รูปแบบการจัดการอุดมศึกษาวิถีพุทธสำหรับแม่ชี: กรณีศึกษา มหาปชาบดีเถรีวิทยาลัย จังหวัดนครราชสีมา (THE EDUCATIONAL MANAGEMENT SCHEME OF BUDDHIST HIGHER EDUCATION FOR NUNS: A CASE STUDY IN MAHA PACHABODEE THEREE COLLEGE, NAKHON RATCHASIMA) - Puncreobutr, Vichian (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2013)
การวิจัยเรื่องรูปแบบการจัดการอุดมศึกษาวิถีพุทธสำหรับแม่ชี กรณีศึกษา มหาปชาบดีเถรีวิทยาลัย จังหวัดนครราชสีมา มีวัตถุประสงค์เพื่อศึกษารูปแบบที่ใช้ในการจัดการอุดมศึกษาวิถีพุทธสำหรับแม่ชี ในประเทศไทย กรณีศึกษา มหาปชาบดีเถรีวิทยาลัย จังหวัดนครราชสีมา การวิจัยนี้เป็นการวิจัยเชิงคุณภาพ โดยใช้วิธีการสังเกตแบบมีส่วนร่วมและการสัมภาษณ์เชิงลึกกับผู้ให้ข้อมูลหลัก รวม 3 กลุ่ม รวม 68 คน ประกอบด้วย อาจารย์และผู้บริหาร นักศึกษาและศิษย์เก่า ผู้เกี่ยวข้องและแม่ชีในสถาบันอื่นๆ ได้ผู้ให้ข้อมูลหลักรวม 11 คน ผลการศึกษาพบว่า รูปแบบที่ใช้ในการจัดการอุดมศึกษาวิถีพุทธสำหรับแม่ชี ในประเทศไทย กรณีศึกษา มหาปชาบดีเถรีวิทยาลัย จังหวัดนครราชสีมา ในการสร้างแม่ชีรุ่นใหม่ให้กับสังคม ที่ได้มาจากการมีศรัทธาในพุทธศาสนาตั้งแต่ต้น ด้วยการดำเนินการ ดังนี้ 1) การรับสมัคร รับผู้สำเร็จการศึกษาชั้นมัธยมศึกษาปีที่ 6 หรือเทียบเท่าทั้งที่บวชเป็นแม่ชีแล้ว และยังไม่ได้บวชเป็นแม่ชีเข้าศึกษาทั้งในลักษณะบวชเป็นแม่ชี และเป็นอุบาสิกา 2) กิจกรรมการเรียนรู้ ประกอบไปด้วย กิจกรรมการเรียนรู้ทางโลกในระดับปริญญาตรี และกิจกรรมที่เป็นกิจของแม่ชีที่ศึกษาและปฏิบัติตนตามพระธรรมวินัย 3) การบริหารการศึกษา ใช้ทั้งหลักการการบริหารวิถีพุทธ การบริหารตามแนวพุทธธรรม และการบริหารตามภารกิจอุดมศึกษา 4) หลักการเรียนรู้ ให้ผู้เรียนเรียนรู้ผ่านการพัฒนา การกิน การอยู่ การดู การฟัง และมีวัฒนธรรมที่อาศัยพรหมวิหาร และอิทธิบาท เป็นฐานดำเนินชีวิต 5) หลักการพัฒนาผู้เรียน พัฒนาผู้เรียนตามลักษณะแห่งปัญญาวุฒิธรรม 4 ประการคือ การอยู่ใกล้ผู้รู้ การเอาใจใส่ศึกษา การคิดวิเคราะห์พิจารณา และการนำไปใช้ในชีวิตประจำวัน 6) หลักการจัดสภาพแวดล้อมทางการเรียน ครอบคลุมทั้ง 5 ด้าน คือ ด้านกายภาพ กิจกรรมพื้นฐานวิถีชีวิต การเรียนการสอน บรรยากาศและสัมพันธภาพ และการบริหารจัดการ 7) หลักธรรมที่ใช้ในการบริหารตนเองของผู้บริหาร อาจารย์ นักศึกษา ปลูกฝังให้ใช้หลักธรรม ธรรมทำให้งาม สันโดษ และอริยทรัพย์ 8) หลักธรรมที่ใช้ในการบริหารคน คือ พรหมวิหาร อธิปไตย และทศพิธราชธรรม 9) หลักธรรมที่ใช้ในการบริหารงาน คือ พละ และสัปปุริสธรรม คำสำคัญ: การศึกษาสำหรับแม่ชี การจัดการอุดมศึกษาวิถีพุทธ The objective of the presented work is to study the educational management scheme of Thailand’s Buddhist higher education for nuns; a case study in Maha Pachabodee Theree College, Nakhon Ratchasima. This qualitative research studied 11 people in three different groups namely lecturers and managers, students and alumni, accomplices and nuns from other institutes. The participant observation method and in-depth interview method were used to collect the data. The results showed that educational management of Thailand’s Buddhist higher education for nuns in Maha Pachabodee Theree College for educating new generation of nuns, who originally believe in Buddhist, can be divided into 9 schemes. First scheme–enrollment, the enrollment is opened for all students who graduated from secondary school (grade 12) or equal. The enrolled students can be ordained nuns or non-ordained female and they can decide either they want to become nuns or laywomen during their study. Second scheme–learning activities, the learning activities are consisted of both secular activities and religious activities in which nuns need to be done follow Dhammavinaya. Third scheme–educational management, educational management is composed of Buddhist-path management, management follows Buddha’s teaching and management follows the mission of higher education. Fourth scheme–learning process, students always learn by improving their living-style, observation, and listening. They also need to have good living culture, four principles virtuous and Iddhippada as their living principle. Fifth scheme–student improvement, all students can be improved follow the concepts of virtues conducive to growth that composed of association with a good and wise man, listening to the good teaching, critical reflection, and practice in perfect conformity to the Dharma or to the principle. Sixth scheme–learning environment, a good learning environment need to cover five aspects namely good physical conditions, good basic living activity, good teaching and learning, good environment and relationship, and good management. Seventh scheme–individual dharmic principle, everyone including managers, lecturers and students needs to have dharma, gracing virtues, contentment, and seven noble treasures. Eighth scheme–people management, dharma for people management includes four principles virtuous, three supremacy and ten virtues of the king. Ninth scheme–work management, dharma for work management includes five powers and seven virtues of the righteous. Keywords: Education for nuns, Buddhist higher education